2021
DOI: 10.3389/fgene.2021.743833
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Case of Epileptic Disorder Associated With a Novel CNTN2 Frameshift Variant in Homozygosity due to Maternal Uniparental Disomy

Abstract: Background: Contactin 2, encoded by CNTN2 on chromosome 1q32.1, is a neural-specific glycoprotein and plays important roles in neurodevelopment. A deleterious homozygous variant in the CNTN2 gene was previously reported to cause autosomal recessive cortical myoclonic tremor and epilepsy. Since then, there has been no further report confirming the association of CNTN2 and epilepsy. Here, we reported one new case, who presented with epilepsy, carrying a novel homozygous frameshift variant in CNTN2. The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Contactin-2 is a neuronal membrane protein contributing to the organisation of axonal domains, and variants in the corresponding gene CNTN2 (HGNC:2172, MIM *190197) have been associated with autosomal recessive myoclonic epilepsy [ 16 ]. The phenotypic association is, however, still provisional in OMIM, and currently only the initial study by Stogmann et al [ 16 ] and one case report are available [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contactin-2 is a neuronal membrane protein contributing to the organisation of axonal domains, and variants in the corresponding gene CNTN2 (HGNC:2172, MIM *190197) have been associated with autosomal recessive myoclonic epilepsy [ 16 ]. The phenotypic association is, however, still provisional in OMIM, and currently only the initial study by Stogmann et al [ 16 ] and one case report are available [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…It works together with contactin-associated protein-like 2 to form a scaffold that accumulates voltage-gated potassium channels at the juxtaparanodes, which are crucial for maintaining membrane potential and modulating action potential frequency during repetitive firing. To date, 13 mutations in the CNTN2 have been associated with epilepsy and FAME5, including 7 missense mutations, splice variants, and 2 small deletions ( Chen et al, 2021 ). In the present study, we have identified a missense homozygous variant CNTN2 c.1699G>T in 3 diseased individuals of the affected family EP-4, that leads to a change in the amino acid p.Glu567Ter in the 6th laminin G-like C domain of the CNTN2 protein (NP_005067.1).…”
Section: Discussionmentioning
confidence: 99%
“…The UPD can cause disease not only through imprinting defects but also through homozygous exposure to recessive genes ( Chen et al, 2021 ). It is currently believed that imprinted genes exist on chromosomes 6, 7, 11, 14, 15, and 20 (Patten et al, 2014).…”
Section: Discussionmentioning
confidence: 99%